2016
DOI: 10.3906/sag-1504-37
|View full text |Cite
|
Sign up to set email alerts
|

The effects of conscious sedation with nitrous oxide/oxygen on cognitive functions

Abstract: The aim of this study was to investigate the effects of conscious sedation with 40% nitrous oxide/oxygen (N 2 O/O 2 ) on cognitive functions. Materials and methods:Forty dental patients referred to the sedation unit at Gazi University Faculty of Dentistry Department of Oral and Maxillofacial Surgery received a combination of 40% N 2 O/O 2 inhalation for conscious sedation. Psychometric tests were applied three times: before sedation, during sedation, and at the end of the recovery, for assessing cognitive func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
8
0
3
Order By: Relevance
“… 3 It was previously reported that N 2 O might induce cognitive impairment when used as an anesthetic. 4 , 5 We present a case report in which a patient presented with encephalatrophy with cognitive dysfunction caused by the recreational use of N 2 O. Encephalatrophy with impaired cognitive function caused by N 2 O recreational use has not been reported previously. This case report is the first to report encephalatrophy accompanied by altered cognitive functioning apart from peripheral neuropathy following intense N 2 O abuse.…”
Section: Introductionmentioning
confidence: 91%
“… 3 It was previously reported that N 2 O might induce cognitive impairment when used as an anesthetic. 4 , 5 We present a case report in which a patient presented with encephalatrophy with cognitive dysfunction caused by the recreational use of N 2 O. Encephalatrophy with impaired cognitive function caused by N 2 O recreational use has not been reported previously. This case report is the first to report encephalatrophy accompanied by altered cognitive functioning apart from peripheral neuropathy following intense N 2 O abuse.…”
Section: Introductionmentioning
confidence: 91%
“…Nitrous oxide itself does not cause severe respiratory inhibition, but it prevents the physiological response to hypoxia at high concentrations (50%) 2. The study reported that memory impairment, learning difficulties and psychomotor activity were reduced with subanaesthetic concentrations of nitrous oxide 9. Dreyfus et al reported the development of chronic toxic encephalopathy with cognitive decline as a result of chronic exposure to nitrous oxide in two anaesthetists who constantly worked in an operating room.…”
Section: Introductionmentioning
confidence: 99%
“…Samur Ergüven y cols. 76 en su trabajo sobre 40 pacientes obtuvieron unos resultados similares a los nuestros en cuanto a saturación de oxígeno y pulso y algo menores en presión arterial sistólica y diastólica, sin ser significativo y dentro de la normalidad, como muestra la tabla 14.…”
Section: Paciente Con Ansiedad Elevadaunclassified
“…También siguen la técnica de titulación Samur Ergüven y cols. 76 en su estudio de 40 pacientes con un 40% de óxido nitroso de máxima concentración, con un tiempo de recuperación de menos de 5 minutos tras fin de administración.…”
Section: Paciente Con Ansiedad Elevadaunclassified
See 1 more Smart Citation